2014
DOI: 10.1016/s0254-6272(14)60092-3
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study on the associations between lifestyle-behavioral risk factors and phlegm-wetness constitution

Abstract: Light diet can decrease the risk of being phlegm-wetness constitution, and bad lifestyle behaviors such as sleeping early and getting up late, sleeping erratically, fatty food, barbecued food or sweet food intake, tobacco and liquor consumptions, and less physical activities can increase the risks of becoming phlegm-wetness constitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…The hypomethylated genes (BCL11B, HLA-C, FOXP1, FOXP1) were mainly involved with immunological and inflammatory diseases [44]. It was noteworthy that these molecular features are consistent with previous publications and clinical observations in TCM [16, 44, 45]. In this experiment, the findings were limited by the relatively small numbers of samples.…”
Section: Discussionsupporting
confidence: 87%
“…The hypomethylated genes (BCL11B, HLA-C, FOXP1, FOXP1) were mainly involved with immunological and inflammatory diseases [44]. It was noteworthy that these molecular features are consistent with previous publications and clinical observations in TCM [16, 44, 45]. In this experiment, the findings were limited by the relatively small numbers of samples.…”
Section: Discussionsupporting
confidence: 87%
“…Vascular damage appears to become worse with the accumulation of phlegm, which results in ischemic stroke. Furthermore, in our study, patients with PSIC syndrome were found to have a higher percentage of drinking history, which is concurrent with the study by Zhu et al [36], which stated that the risk factors of a phlegmwetness body type were caused by alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
“…Alcohol might also induce hypoglycemia. Tobacco and liquor consumption also indicate bad lifestyle behaviors, which lead to weight loss. Previous research has shown that individuals might be lean because of the chronic accumulation of metabolic, inflammatory and pathological conditions caused by long‐term exposure to smoking, drinking and unhealthy diets.…”
Section: Discussionmentioning
confidence: 99%